Analysis of dysarthria in a 55-year-old female patient with multiple sclerosis by means of an IT tool based on respiratory and phonatory examination – a case study - Warmbier, Wojciech A.; Popiel, Małgorzata; Guzik, Agnieszka; Drużbicki, Mariusz; Bartosik-Psujek, Halina (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. There are no available objective tools for assessing dysarthric disorders in the course of multiple sclerosis (MS). The aim of the study is to analyse a case of mixed dysarthria in a 55-year-old female patient in the course of secondary progressive MS and to present the severity of the patient’s dysarthric disorder in contrast with the control group as evaluated by means of an IT tool based on respiratory and phonatory examination. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 55-year-old patient was admitted to the Clinic of Neurology with the Stroke Unit due to a worsening condition in the course of MS. She was examined with an objective tool for respiratory and phonatory disorders. Her results were, then, compared to those of 24 healthy individuals from the control group, matched in terms of sex and age. Following speech parameters were analysed: phonetics of utterances, number of produced syllables per breath during the execution of individual texts, sound quality, intonation, and the total performance time of each. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The analysed case indicates that the developed objective IT tool is a promising diagnostic method that can facilitate diagnosis and can be used in clinical practice.